DEPRIVATION AND CITIZENSHIP IN IRAQI POETRY 2003-2019 (AN ANALYTICAL STUDY IN THE LIGHT OF CULTURAL CRITICISM) - Alaa Talib Abdullah; Emad Jasim Salman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The poems of exile summarize the pain of poets deported from their homelands in line with their ideas and human experiences. From the usual nostalgia in exile poems for the emergence of what is more important than the existence of exceptional circumstances that made most poets deviate towards discussing the diaries of countries that burn in civil wars and the high number of bombings and killings on identity with the failure of building democracy, which was the dream of most Iraqis. Politicians with language close to directness and may not stray from superficiality in some poetic passages, taking advantage of their alienation from the homeland in the freedom to say without fear or fear, but many of them depended on following the news. Through the media and social networking sites, so that their notice approached a news bulletin or an echo of Arab and international news bulletins showing the tragic, exaggerated picture of Iraq. The great journey to exile appears after the coup of February 8, 1963, so Iraq witnessed mass migrations after the Baath party assumed the sovereignty of power in Iraq. Many poets such as Baland Al-Haidari, Abdul Wahab Al-Bayati, Saadi Youssef, and Muzaffar Al-Nawab left, as well as the novelist Ghaeb Tohma Furqan and the world Abdul Mighty Abdullah.